Remarks on Residual Stress Measurement by Hole-Drilling and Electronic Speckle Pattern Interferometry - Claudia Barile; Caterina Casavola; Giovanni Pappalettera; Carmine Pappalettere (The Scientific World Journal)
Hole drilling is the most widespread method for measuring residual stress. It is based on the principle that drilling a hole in the material causes a local stress relaxation; the initial residual stress can be calculated by measuring strain in correspondence with each drill depth. Recently optical techniques were introduced to measure strain; in this case, the accuracy of the final results depends, among other factors, on the proper choice of the area of analysis. Deformations are in fact analyzed within an annulus determined by two parameters: the internal and the external radius. In this paper, the influence of the choice of the area of analysis was analysed. A known stress field was introduced on a Ti grade 5 sample and then the stress was measured in correspondence with different values of the internal and the external radius of analysis; results were finally compared with the expected theoretical value.